Cholinesterase Enzyme Association with Quality of Life Among Farmers in Khong Chai District, Kalasin Province, Thailand - Supasin Deeraksa; Mayuree Suwunnakhot; Khanittha Madngammuang (Jurnal Keperawatan Indonesia)
The agricultural sector in Thailand faces challenges that impact farmers' health and quality of life. This study examines the quality of life, cholinesterase enzyme levels, and factors associated with quality of life among farmers in Khong Chai District, Kalasin Province, Thailand. This cross-sectional analytical study was conducted using systematic random sampling. The respondents had a mean age of 54.97 ± 10.50 years (range 25–75 years) and comprised 75.56% females (n = 204), 24.44% males (n = 66). Data collection included demographic information, blood samples to assess cholinesterase enzyme safety levels, and responses to the World Health Organization Quality of Life Brief-Thai (WHOQOL-BREF-THAI) questionnaire. Data were analyzed using descriptive and inferential statistics. Multiple linear regression was utilized to identify factors associated with WHOQOL-BREF-THAI scores, presenting adjusted mean differences, 95% confidence intervals (95% CI), and p-values. The mean of WHOQOL-BREF-THAI score was 89.97 ± 10.34. Factors associated with higher quality of life scores included gender (male: 3.06; p = 0.032), agricultural land size of 10 Rai (1600 m2) or more (2.55; p = 0.039), frequency of cholinesterase blood testing (1 time: 3.01; never: 3.40; p = 0.039; reference: 2 times or more), and blood cholinesterase enzyme safety levels (unsafe: 1.69; p = 0.037). These findings highlight the need for interventions to reduce risk factors, particularly among farmers with unsafe cholinesterase enzyme levels, to improve the quality of life in this population.